A Rare Clinical Case: Giant Splenic Artery Aneurysm and Its Successful Endovascular Treatment - Alptekin Yasim; Hakan Kara; Erdinc Eroglu (Case Reports in Vascular Medicine)
Objectives. The true giant splenic artery aneurysms are extremely rare and can be fatal. Although surgical approach has been the standard of care in the past, endovascular methods gained more importance in recent years. Background. We describe a case with true giant splenic artery aneurysm, treated with endovascular approach. Methods. A 68-year-old female patient with abdominal pain admitted to our clinic had true splenic artery aneurysm (14 × 10 × 9 cm). We decided on endovascular treatment using vascular plug and the treatment was performed successfully. Conclusions. Due to high mortality and morbidity in open surgery, endovascular treatment of giant splenic artery aneurysm is a better treatment option.